Investigating EFL Teachers’ Perceptions Towards Professional Engagement - Inka Lutfiatun Nida; Sri Kusuma Ningsih (English Education Department at FKIP Nommensen University, 2023)
Teacher professional engagement is essential in driving success in education, both in student and teacher personal development. This study aims to determine EFL teachers' perceptions of professional engagement in terms of commitment to the profession, devotion to the profession and dedication to students. The data was collected from 107 EFL teachers. This study uses a quantitative descriptive approach. The Teacher Professional Engagement Scale Questionnaire (TPES) was used to collect the data. The results of this study, it was found that the subscale of teachers' commitment to their profession obtained the highest results with 94.4% strongly agree. This study also helpful for showing how much teachers' professional engagement level is in their work.